The Effect of Anti-Thyroid Peroxidase Antibodies on Pregnancy Outcomes in Euthyroid Women - Monika Meena; Seema Chopra; Vanita Jain; Neelam Aggarwal (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Thyroid autoimmunity can have an adverse impact on the outcome of the pregnancy. Although the adverse effects of antithyroid antibodies have been well studied in hypothyroid women, their effects in euthyroid women are not well evaluated. Aim: The study was conducted to assess the overall prevalence of anti-Thyroid Peroxidase (anti-TPO) antibodies in pregnant women and the effect of anti-TPO positivity on the outcome of pregnancy in euthyroid women. Materials and Methods: One thousand Indian women, in their first trimester were screened for anti-TPO antibodies to know the prevalence. Of this, euthyroid women who were positive for the presence of anti-TPO antibody were selected and their obstetric history was recorded. These women were followed up and the incidences of maternal and foetal complications were recorded. The complications were compared with the past obstetric history and outcomes in parity and gestation matched controls (anti-TPO negative). Results: The prevalence of anti-TPO positivity was 11% (n=110). Out of the positives, those with elevated Thyroid Stimulating Hormone (TSH) were 6.5%. The prevalence of euthyroid women who were anti-TPO positive was 4% (n=40). Anti-TPO positive, euthyroid females had a higher prevalence of infertility, anaemia and preterm delivery as compared to the controls (p<0.0001). No differences were observed between the two groups in terms of history of abruption recurrent abortions, intrauterine growth restriction, postpartum haemorrhage, symptomatic hypothyroidism, hypertensive disorders of pregnancy and foetal complications. Conclusion: Anti-TPO positivity is common in pregnant women. Anti-TPO positive euthyroid females had a higher prevalence of infertility, anaemia as well as preterm delivery. Our results indicate that anti-TPO screening in pregnancy, may aid in early identification of the women at risk.